Maternal monosaccharide diets evoke cognitive, locomotor, and emotional disturbances in adolescent and young adult offspring rats - Witek, Kacper; Wydra, Karolina; Suder, Agata; Filip, Małgorzata (Frontiers in Nutrition, 2023)
Anxiety and depression are the most common mental disorders affecting people worldwide. Recent studies highlighted that a maternal high-sugar diet (HSD) could be considered a risk factor for neurobehavioural dysregulations, including mood disorders. Increasing the consumption of added sugar in food with refined fructose/glucose in the human diet can not only increase the risk of metabolic disorders but can also change susceptibility to mental disorders. Furthermore, a few papers have reported disabilities in learning and memory among offspring after maternal HSD, thus suggesting a relationship between maternal nutrition and offspring neurogenesis. In this study, we evaluated the impact of maternal monosaccharide consumption based on a glucose (GLU) or fructose (FRU) diet during pregnancy and lactation in adolescent and young adult offspring rats of both sexes on cognitive, locomotor and emotional disturbances. Locomotor activity, short-term memory, anxiety-like and depressive-like behaviour were evaluated in the offspring. We report for the first time that the maternal GLU or FRU diet is sufficient to evoke anxiety-like behaviour among adolescent and young adult offspring. Moreover, we showed that maternal monosaccharide diets lead to hyperactivity and depressive-like behaviour in male adolescent rats. We point out that a maternal FRU diet significantly enhanced novelty-seeking behaviour only in young adult males. Our novel findings indicate that the maternal monosaccharide diet, especially a diet enriched in FRU, results in strong behavioural alterations in offspring rats at early life stages. This study also reveals that males are more susceptible than females to hyperactivity and anxiety- and depressive-like phenotypes. Collectively, these results suggest that maternal monosaccharide consumption during pregnancy and lactation is an important factor that affects the emotional status of offspring.